PENERAPAN ALGORITMA FISHER-YATES SHUFFLE PADA GAME KUIS PEMBELAJARAN ILMU SINTAKSIS BAHASA INDONESIA - T. Zulfa Eldiansyah, - (2019)
Quiz games Indonesia language syntax is a learning application which explains that the syntax applies linguistics that investigates the structure of sentences and sentence arrangement of steel. In the menu there are test questions with multiple choice of four formats. Users simply choose the one answer which is the menu. The purpose of this application development discusses designing game learning Algorithm that implements the Fisher-Yates Shuffle for randomization reserved. To make this learning quiz application using the Web service as a data exchange architectures between clients with server. And the Fisher-Yates algorithm using the Shuffle as a function of randomization on exam questions. Application testing is performed with the black box to test each system. After successful testing done then it can be concluded that the application of the Fisher-Yates Shuffle algorithm is successfully applied in this quiz game to determine a solution based on randomization test results as much as ten times the experiment